Labour productivity and rice production in Bangladesh - Sheikh Selim (Cardiff University, Cardiff Business School, 2010)
In this paper we examine the significance of labour productivity and use of inputs in explaining technical efficiency of rice production in Bangladesh. We find that higher labour productivity can stimulate high efficiency gains, but increased use of inputs (except land) induces negative marginal effect on technical efficiency. While more use of land, improved seeds and fertilizers contributes to the rate of labour-productivity induced marginal efficiency gain, any additional labour depresses this rate. Given the agricultural policy reform history in Bangladesh, our findings imply that rather than providing input subsidy or output price support, future reforms should put more emphasis on providing incentives to enhance labour productivity and encourage formalization of the agricultural labour market.
Keywords: C33; C51; O13; Q12; 330; Stochastic frontier; non-neutral frontier; technical efficiency; Arbeitsproduktivität; Technische Effizienz; Reisanbau; Schätzung; Bangladesch